(untitled) (Journal of Computational Mathematics, 1990)
A completely exponentially fitted difference scheme is considered for the singular perturbation problem: ε U^''+a(x) U^'-b(x) U=f(x) for 0 x 1, with U(0), and U(1) given, ε (0,1] and a(x) α 0, b(x)≥ 0. It is proven that the scheme is uniformly second-order accurate.